Art in the Pre-Hispanic Southwest An Archaeology of Native American Cultures. - Palonka, Radosław (Issues in Southwest archaeology., 2022)
This book examines the development of pre-Hispanic Native American cultures in the American Southwest and Mexican Northwest from the Paleoindian period until the appearance of the first Europeans in the sixteenth century through studies of settlements, rock art, and pottery iconography.